Participation in contract farming and farm performance: Insights from cashew farmers in Ghana - Caroline Dubbert (Agricultural Economics, 2019)
The global demand for cashew nuts continues to increase steadily. However, many African countries face difficulties in marketing and adding value to the product. Using recent survey data of 391 cashew farmers in Ghana, this paper contributes to the growing evidence on the significance of contract farming (CF) in improving the welfare of rural households in developing countries. Specifically, the paper analyzes the factors that influence cashew farmers' decisions to participate in CF, and the impact of participation on farmers' performance. We employ a recently developed switching regression model with endogenous explanatory variables and endogenous switching to control for selection bias caused by observable and unobservable factors. The empirical results show that participation in CF significantly increases labor productivity and price margins, as well as cashew yields, and net revenues. A disaggregated analysis of the sample into farm size categories reveals that small-sized cashew farms tend to benefit more through CF, compared to medium- and large-sized farms.
Keywords: 330; Africa; cashew; contract farming; impact assessment; value chain; C34; J24; L24; O13; Q13